Physico‐chemical characterization of humic‐metal‐phosphate complexes and their potential application to the manufacture of new types of phosphate‐based fertilizers. Issue 2 (15th November 2013) - Urrutia, Oscar; Erro, Javier; Guardado, Inaki; San Francisco, Sara; Mandado, Marcos; Baigorri, Roberto; Claude Yvin, Jean; Ma Garcia‐Mina, José
Abstract: The aim of this review is to describe the main physicochemical characteristics of diverse types of humic‐metal‐phosphate acid complexes. The effects of these complexes on phosphorus (P) fixation in soils with different pH values and physicochemical features and on plant phosphorus uptake are also discussed. Humic‐metal‐phosphate complexes have apparent stability constants in the same range as those of metal‐humic complexes, in solutions with diverse pH and ionic‐strength values. Likewise, the molecular‐size distribution of humic‐metal‐phosphate complexes as a function of pH is similar to that of potassium or sodium humates and metal‐humic complexes. Humic‐metal‐phosphate complexes are able to decrease phosphate fixation in soils and increase plant growth and phosphate uptake. Phosphorus fertilizers containing humic‐metal‐phosphate complexes proved to be efficient to improve plant growth and P uptake with respect to conventional fertilizers such as single superphosphate. The values of parameters related to plant phosphorus‐utilization efficiency (PUt E) suggest that the regulation of root acquisition of phosphate from these complexes could involve the interregulation of a system for the optimization of metabolic P utilization in the shoot and another system involving stress responses of roots under phosphorus deficiency.